Preliminary Functional Outcomes and Quality of Life after Tongue Reconstruction with the Vastus Lateralis Myofascial Free Flap - De Virgilio, Armando; Costantino, Andrea; Pellini, Raul; Petruzzi, Gerardo; Mercante, Giuseppe; Zocchi, Jacopo; Mondello, Tiziana; Conti, Valerio; Spriano, Giuseppe (Facial Plastic Surgery, 2021)
The aim of the present study is to report our preliminary experience with the vastus lateralis myofascial free flap (VLMFF) for tongue reconstruction according to tongue and donor site functional outcomes. Twelve consecutive patients (F: 5; median age: 54.0 years, interquartile range or IQR 42.75–69.0) were included. The validated European Organization for Research and Treatment of Cancer of the Head and Neck 35 Quality of Life Questionnaire (EORTC QLQ-H&N35) and the performance status scale for head and neck cancer (PSS-HN) questionnaires were used to assess the health-related quality of life (HRQOL). The lower extremity functional scale (LEFS) was used to self-report the donor area function. All patients were successfully treated, and no VLMFF failure was detected during a median follow-up period of 10.5 months (IQR: 6.5–33.0). The HRQOL showed a median EORTC QLQ-H&N35 score of 56.0 (IQR: 50.0–72.5). The median PSS-HN score was 80.0 (IQR: 45.0–95.0), 75.0 (IQR: 62.5–100.0), 75.0 (IQR: 62.5–100.0) for “Normalcy of Diet,” “Public Eating,” and “Understandability of Speech,” respectively. The self-reported function of the lower extremities (donor area) showed a median LEFS of 59.0 (IQR: 32.5–74.0). This study reports optimistic data regarding the functional and quality of life outcomes after tongue reconstruction using VLMFF. Prospective controlled studies are needed to demonstrate advantages and disadvantages when compared with other reconstructive techniques.
Keywords: microsurgery; free flap reconstruction; functional outcome; quality of life